1991
DOI: 10.1105/tpc.3.6.583
|View full text |Cite
|
Sign up to set email alerts
|

Developmental analysis of elongation factor-1 alpha expression in transgenic tobacco.

Abstract: The developmental regulation of the translational elongation factor EF-1 alpha has been analyzed in tobacco. A gene fusion was constructed consisting of the 5' and 3' regions of the tomato genomic clone LeEF-A from the EF-1 alpha gene family and the beta-glucuronidase coding region. Analysis of the transgenic plants containing this chimeric gene demonstrated that the tomato LeEF-A flanking sequences were sufficient to confer expression patterns similar to those of the endogenous tobacco EF-1 alpha gene. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The activity of a partially puri®ed EF-2 from wheat germ has been examined (Smailov et al 1993). However, another family of elongation factors of the 1-a type, homologous to the bacterial factor EF-Tu, has been implicated in the control of plant development through the regulation of protein synthesis (Ursin et al 1991). EF-1a is thought to aect plant growth and dierentiation by interacting with microtubules (Durso and Cyr 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of a partially puri®ed EF-2 from wheat germ has been examined (Smailov et al 1993). However, another family of elongation factors of the 1-a type, homologous to the bacterial factor EF-Tu, has been implicated in the control of plant development through the regulation of protein synthesis (Ursin et al 1991). EF-1a is thought to aect plant growth and dierentiation by interacting with microtubules (Durso and Cyr 1994).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in tobacco plants showed that its expression was higher in younger, developing tissues than in older or more mature tissues [41]. Moreover, the same gene was also highlighted as a candidate gene for proteomic analysis of shoot apical meristem transition from dormancy to activation in Cunninghamia lanceolata (Lamb.)…”
Section: A High Input Of Energy Is Required During Bud Sprouting In Cmentioning
confidence: 96%
“…In tomato (Pokalsky et al, 1989), tobacco (Ursin et al, 1991;Marty et al, 1993), and possibly Arabidopsis (Curie et al, 1993), elevated levels of EF-lu gene expression were indicated in developing tissues. Auxin (Ursin et al, 1991), low temperature (Dunn et al, 1993), and light (Aguilar et al, 1991) appear to modulate expression of some EF-lu genes, and multigene families are present in severa1 plants (Axelos et al, 1989;Pokalsky et al, 1989;Aguilar et al, 1991;Dunn et al, 1993). A gene family has been found in carrot cells as well (Kawahara et al, 1992), and Figure 46 presents data consistent with this finding.…”
mentioning
confidence: 99%